2020
DOI: 10.1021/acsomega.0c01844
|View full text |Cite
|
Sign up to set email alerts
|

Study of Electronic and Vibrational Structures of Reduced, Neutral, and Oxidized Ni3(dpa)4X2 Using Density Functional Theory and Raman Spectroscopy

Abstract: The electronic and vibrational structures of trinickel metal string complexes [Ni3(dpa)4X2]1–,0,1+ (X = Cl, NCS) were investigated using both theoretical calculations and spectroscopic methods. We used the density functional theory (DFT) method B3LYP*-D3, including less exact exchange energy and the van der Waals interaction of metal ions, to obtain the geometries and vibrational structures, which were found to be in excellent agreement with the experimental data. The ground state of Ni3(dpa)4X2 is an antiferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…All geometry optimizations and spectra calculations were performed using the Gaussian 16 package [23] . The modified hybrid functional B3LYP*‐D3 was employed because the calculated Raman spectra resulting from this method agreed with the experimental spectra for some trinuclear HMSCs [24,25] . In these calculations, 15 % of Hartree‐Fock term and the unrestricted methods were used for the HMSCs.…”
Section: Methodsmentioning
confidence: 99%
“…All geometry optimizations and spectra calculations were performed using the Gaussian 16 package [23] . The modified hybrid functional B3LYP*‐D3 was employed because the calculated Raman spectra resulting from this method agreed with the experimental spectra for some trinuclear HMSCs [24,25] . In these calculations, 15 % of Hartree‐Fock term and the unrestricted methods were used for the HMSCs.…”
Section: Methodsmentioning
confidence: 99%
“…Both s‐ and u‐geometries were optimized using the GAUSSIAN package. [ 20 ] The B3LYP*‐D3 method was employed in the Co 3 system because the agreement in both the optimized geometries and the vibrational frequencies of Ni 3 (dpa) 4 Cl 2 with the experimental data was better than that of the BP86 and B3LYP methods. [ 21 ] B3LYP*‐D3 includes a less exchange integral and the correction method D3 for van der Waals interaction between metal ions.…”
Section: Experimental and Computation Detailsmentioning
confidence: 99%
“…Since the first report on the synthesis and structural characterization of [Cu 3 (dpa) 4 Cl 2 ] was published in 1990, a series of studies have been reported by Peng’s group, Berry’s group, , and Cornia’s group , to develop the structurally similar compounds and to study their molecular structures and physicochemical properties such as magnetic properties, electrical conductivity, and electrochemical properties. Cotton et al found that [Cr 3 (dpa) 4 Cl 2 ] exhibits an asymmetric configuration in benzene and toluene solvents, but in a more polar tetrahydrofuran solvent, it has a symmetric configuration with equal Cr–Cr bonds.…”
Section: Introductionmentioning
confidence: 99%